FULL DAY SCHOOL MANAGEMENT IN IMPROVING THE CHARACTER OF STUDENTS AT AL AMIN ISLAMIC HIGH SCHOOL SIDOARJO - Anya Olimvia Wimpi Suwandi Putri; M. Athoiful Fanan (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This research is about full day school management in improving the character of students at Al Amin Sidoarjo Islamic High School. This study aims to describe the management of full day school in improving the character of students at SMA Islam Al Amin Sidoarjo. This type of research is qualitative research. Which includes interviews, observations and documentation. Data sources are taken from interviews, observations and documentation with principals, vice principals for curriculum, teachers and students. The result is that full day school management can improve the character of students at Al Amin Sidoarjo Islamic High School well. Starting from planning, organizing, implementing to supervising. In full day school there are learning activities, integrated curriculum and learning time. This certainly can improve the character of students with 5 characters applied, namely religious, independent, integrity, nationalist and gotong royong. The benefit, of course, is that full day school management is able to improve the character of students at Al Amin Sidoarjo Islamic High School.